Les anarchistes et la prostitution : perspectives historiques - Francis Dupuis-Déri (Genre, Sexualité et Société)
Anarchist networks throughout North America and Europe are currently engaged in debates on the topic of prostitution. Despite their diversity, a discourse analysis on this subject about anarchists from the late 19th century to the middle of the 20th reveals certain converging outlooks and influential trends. Most anarchists of that period seemed to agree that the misery engendered by capitalism is what drove poor women into prostitution. For some, prostitution bears comparison with marriage or various wage-earning trades, but it remains the most unfair and violent form of exploitation. Solutions proposed by anarchists in the past included executing procurers, helping prostitutes to unionize, setting up centres for individuals wishing to give up prostitution, and assisting prostitutes in establishing self-managed workplaces.